PENGARUH DISIPLIN, KOMPETENSI, DAN MOTIVASI TERHADAP KUALITAS PELAYANAN PETUGAS PAJAK KENDARAAN BERMOTOR DI SAMSAT KLATEN - Rahmawati, Restia; Badrudin, Rudy (Jurnal Ekonomi Dan Bisnis, 2023)
This study aims to explain the effect of work discipline, employee competence, and work motivation on the service quality of motor vehicle tax officer at SAMSAT Klaten. Data collection techniques used in this study is questionnaires to pewajib pajak at SAMSAT Klaten. The sample in this study were 100 responden with simple random sampling. The data analysis techniques in this study include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, F test, t test, and coefficient determination test. The result of the study are variable effect of work discipline, employee competence, and work motivation together or simultaneously have a significant effect on Service Quality of motor vehicle tax officer at SAMSAT Klaten. Partially, each variable, namely work discipline, employee competence, and work motivation, has a significant effect on Service Quality of motor vehicle tax officer at SAMSAT Klaten. The service quality variable can be explained by work discipline, employee competence, and work motivation which are explained by the independent variable of 78,8% and the others are influenced by another variable.